2019
DOI: 10.1111/jphp.13176
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxy mansonone G as an anticancer agent in estrogen receptor-positive and endocrine-resistant breast cancer

Abstract: Objectives To study anticancer effects, underlying mechanism and safety of ethoxy mansonone G (EMG) which is the potent derivative of mansonone G (MG) in breast cancer cells. Methods Anticancer, antimigration, anti-invasion effects and anchorage-independent growth were investigated by MTT, scratch, matrigel invasion and soft agar assays. Estrogen receptor (ER)-targeted genes and endocrine-resistant genes were assessed by RT-PCR and Western blot. Key findings Ethoxy mansonone G is the most potent MG derivative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…One underused family of cytotoxic natural products is the ortho -quinones. Several low-molecular-weight compounds that contain an ortho -quinone group, such as β-lapachone 8 , tanshinones (I, IIA, IIB and crypto) 9 , mansonones A–G 10 , dunnione 11 , miltirone 12 , salvicine 13 and caryopteron A 14 , display wide antiproliferative effects in vitro. For example, β-lapachone ( 1 , Fig.…”
Section: Mainmentioning
confidence: 99%
“…One underused family of cytotoxic natural products is the ortho -quinones. Several low-molecular-weight compounds that contain an ortho -quinone group, such as β-lapachone 8 , tanshinones (I, IIA, IIB and crypto) 9 , mansonones A–G 10 , dunnione 11 , miltirone 12 , salvicine 13 and caryopteron A 14 , display wide antiproliferative effects in vitro. For example, β-lapachone ( 1 , Fig.…”
Section: Mainmentioning
confidence: 99%
“…With the lack of success of synthetic antibiotics being introduced to the clinic, in recent years, attention has been turned to natural compounds, of both plant and animal origins, as promising candidates [ 1 ]. Therefore, in the quest to find new antibacterial molecules, our study was focused on screening mansonone G, a compound having known to possess a number of medicinal properties [ 9 , 12 14 , 17 , 18 ], and its derivatives, hypothesizing the possibility of finding some molecules that are active against Gram-positive and even Gram-negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds from this botanical source, including the 1,2-naphthoquinones—mansonones—were also found to possess antifungal, antioxidant and larvicidal properties [ 12 ]. Mansonone G, a naturally occurring o -naphthoquinone (5% of CH 2 Cl 2 extract), has been studied by many and found to show antifungal [ 13 ] and anticancer [ 9 , 14 , 15 ] properties. Furthermore, cytotoxicity tests of mansonone G in HCT-116, HepG2, MCF-7 and HeLa cell lines also provided promising results [ 16 ] highlighting its potency as a good candidate for further drug development.…”
Section: Introductionmentioning
confidence: 99%
“…Allyl and phenyl ethers of MG have demonstrated antibacterial activity against Staphylococcus aureus 64 times higher than the parent MG compound 3 . In addition, recent studies have reported that ethoxy and butoxy MGs were more cytotoxic to non-small cell lung cancer and breast cancer cells than their parent compound 7 , 8 . Therefore, the present study assessed the cytotoxic activity of MG and its ether analogs on two human colorectal cancer cells lines, HCT-116 cells carrying p53 wild-type and HT-29 cells carrying p53 mutant.…”
Section: Introductionmentioning
confidence: 99%